Acceleration of Strengthening Digital Literacy in the Era of Society 5.0 - Rona Romadhianti; Yosi Wulandari; Ratna Dewi Kartika Sari (Universitas Pendidikan Ganesha, 2021)
The geographical location of schools in coastal areas is certainly very influential on the development of digital literacy in the learning process. This is caused by various obstacles, both material constraints, human resources, and social constraints, which then have an impact on the inhibition of the digital-based learning process. The purpose of this study has three objectives, as follows: To determine the extent to which the use of digital literacy has implications for learning, to find out the obstacles and challenges in the application of digital literacy, and to optimize the application of digital literacy in learning activities. Qualitative analysis was used in this study. The average result of implementing digital literacy in coastal areas has only reached 45% in the learning process. There are also obstacles in its implementation due to limited Human Resources (HR) for both educators and students, lack of facilities and infrastructure, the location of school demographics, management of digital literacy applications that have not been maximized by schools and teachers who drive digital literacy. It can be concluded that the application of digital literacy is still not optimal.